2013
DOI: 10.1016/j.crohns.2012.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasonography: Usefulness in the assessment of postoperative recurrence of Crohn's disease

Abstract: CEUS shows excellent sensitivity and specificity for the diagnosis of postoperative recurrence in CD and can also detect severe recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 35 publications
0
70
0
1
Order By: Relevance
“…Another study also showed that the area under the time-intensity curve obtained after microbubbles injection was the only parameter to discriminate between responders and nonresponders among CD patients during pharmacological treatment (p \ 0.05) [72]. Recently, it was demonstrated that CEUS showed high sensitivity, specificity and accuracy (97, 91, 96%, respectively) for the early detection of endoscopic recurrence after intestinal resection in CD patients, with the simple combination of parietal thickness [5 mm and contrast enhancement [46% [73].…”
Section: Ceusmentioning
confidence: 99%
“…Another study also showed that the area under the time-intensity curve obtained after microbubbles injection was the only parameter to discriminate between responders and nonresponders among CD patients during pharmacological treatment (p \ 0.05) [72]. Recently, it was demonstrated that CEUS showed high sensitivity, specificity and accuracy (97, 91, 96%, respectively) for the early detection of endoscopic recurrence after intestinal resection in CD patients, with the simple combination of parietal thickness [5 mm and contrast enhancement [46% [73].…”
Section: Ceusmentioning
confidence: 99%
“…There are yet few studies concerning this subject, but the results are promising. Biological treatment with anti TNF-α agents was associated with a significant reduction of the intestinal wall diameter and improvement of the transmural vascularization in 50% of the patients [39,69,70]. All US parameters were improved in patients in remission who also had a significant HBI decrease at 3 months after anti TNF-α therapy initiation, showing a good correlation between US markers and clinical signs and symptoms [40].…”
Section: Monitoringmentioning
confidence: 71%
“…At the moment, endoscopy is the gold standard tool in this situation, but lately, US has provided significant credit, with a sensitivity of 89.7% for the detection of recurrent postoperative disease which can be increased by CEUS to 98% [69].…”
Section: Monitoringmentioning
confidence: 99%
“…The sensitivity and specificity for detecting ileal disease was higher compared to colonic disease (Table 4). Both cases (2/10) missed on US were mild endoscopically, possibly not yet exhibiting cross-sectional disease activity [29]. Regardless of imaging modality, mild disease is difficult to detect, given the absence of transmural involvement, as early disease involves the mucosa and this is also reflected here, as there were 2 false negatives versus only 1 false positive (Table 3).…”
Section: Discussionmentioning
confidence: 87%